2022
DOI: 10.1007/s10803-022-05576-1
|View full text |Cite
|
Sign up to set email alerts
|

Provider and Caregiver Satisfaction with Telehealth Evaluation of Autism Spectrum Disorder in Young Children During the COVID-19 Pandemic

Abstract: The present study examines provider and caregiver satisfaction with telehealth evaluation of autism spectrum disorder (ASD) in young children during the coronavirus SARS-CoV-2 (COVID-19) pandemic. A telehealth model of ASD evaluation was implemented with 308 children ages 14 to 78 months between May 2020 to June 2021. Data were gathered from electronic health records, autism-specific telehealth diagnostic tools, and post-evaluation surveys. Overall, the majority of providers and caregivers were satisfied with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…Furthermore, our large sample of children were diverse (with somewhat higher proportion of non-White and Latinx participants than the state census data), especially regarding family socioeconomic status, use of public health insurance, and residing in MUAs. Previous research has highlighted that telemedicine may not address health service access inequities ( Weiner et al, 2021 ); while we cannot rule out this possibility, the present study and related work has demonstrated nonsignificant associations between demographic factors and tele-assessment satisfaction and diagnostic outcome ( McNally Keehn et al, 2021 ; Reisinger et al, 2022 ).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, our large sample of children were diverse (with somewhat higher proportion of non-White and Latinx participants than the state census data), especially regarding family socioeconomic status, use of public health insurance, and residing in MUAs. Previous research has highlighted that telemedicine may not address health service access inequities ( Weiner et al, 2021 ); while we cannot rule out this possibility, the present study and related work has demonstrated nonsignificant associations between demographic factors and tele-assessment satisfaction and diagnostic outcome ( McNally Keehn et al, 2021 ; Reisinger et al, 2022 ).…”
Section: Discussioncontrasting
confidence: 84%
“…Remote clinicians coach caregivers to complete a brief set of activities using toys and materials available within many home environments. When implemented as part of a comprehensive ASD evaluation, including a developmental history and symptom-focused interview, clinicians and caregivers report satisfaction with this method ( Corona et al, 2020 ; Reisinger et al, 2022 ; Wagner et al, 2020 ; Wagner, Weitlauf, et al, 2021 ). Additional studies have demonstrated evidence of diagnostic utility of the TAP.…”
mentioning
confidence: 99%
“…This is because social distancing has brought with it extensive changes in the lives of families, with particular potential impact on many domains of functioning at the same time [ 3 ]. The protective measures undertaken, such as social distancing and interruption of face-to-face activities [ 4 , 5 , 6 , 7 , 8 ], more than preventing the spread of the COVID-19, interrupted a series of therapies and other activities to promote the development of these children. Thereafter, countless families with children and adolescents presenting developmental disability were left out by the impossibility of continuing therapeutic care or face-to-face guidance for follow up [ 5 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Remote health care involves both patients’ evaluation and intervention. Nevertheless, the implementation of remote care programs occurred despite the lack of specific technical directions addressing physical security of the patients, the confidentiality of their data, and ethical aspects involving virtual data management and other investigations about the feasibility of the processes used in remote assessment [ 4 , 5 , 9 , 12 , 13 ]. In this way, for telehealth strategies for children with disabilities to be well targeted and reliable, it is important that remote assessments are effective, and parents feel comfortable with this kind of approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation